Criminalization of the Crisis of Masculinity - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
In the last twenty years, a significant degree of research has been dedicated to the social structure of masculinity, male positioning and practice in gender relations. Social determination of gender differences enables an analytical approach to masculinity through which the effects of various socio-psychological phenomena may be viewed. Variations of masculinity are a part of identity changes, which may be viewed both at the level of individual maturing of adolescents and as a part of complex and mutually linked social processes. In the process of repatriarchalization, but also criminalisation, the traditional patriarchal identity evokes the warrior one in militant masculinity, which offers a return of the lost male dignity. Thus, normal masculinity falls into a crisis of violence, in which lost social positions, threatened existence and destabilised identity are compensated by malicious violence. Criminal behaviour may serve as a resource for a certain type of masculinity.